Inhabiting the cruciform God: kenosis, justification, and theosis in Paul's narrative soteriology - Gorman, Michael J. (William B. Eerdmans Pub. Co, 2009)
Inhabiting the cruciform God : Paul and the question of theosis -- "Although/because He was in the form of God" : the theological significance of Paul's master story (Phil. 2:6-11) -- "Justified by faith/crucified with Christ" : justification by co-crucifixion : the logic of Paul's soteriology -- "You shall be cruciform for I am cruciform" : Paul's trinitarian reconstruction of holiness as theosis -- "While we were enemies" : Paul, the Resurrection, and the end of violence -- Inhabiting the cruciform God : theosis as Paul's narrative soteriology